Approaching literary connectivity: Early reflections on a Shared Reading intervention in the light of postcritical thought - Pihl, Marie‐Elisabeth Lei; Kristensen, Mette Marie; Folker, Anna Paldam; Simonsen, Peter (Orbis litterarum, 2024)
During recent decades, numerous studies have examined uses of art and literature in the context of health care and preventive interventions. In a recent, large‐scale review of current evidence within the field, the World Health Organization (WHO) concluded that art and culture are vital resources for health promotion, and should be included in health care programs and initiatives to a greater extent than is the case today (Fancourt & Finn, 2019). This article zooms in on “Shared Reading,” a literature‐based intervention developed by the Reader Organization. More specifically, we look at a Danish Shared Reading project for male seniors—“Read, Man!”—that aims to reduce loneliness and isolation among men in the age group of 65–75 in view of the fact that men of this age range have increased risk of developing depressive symptoms in connection with retirement (Noh, Kwon, Lee, Oh, & Kim, 2019). A systematic analysis of the project's data has yet to be undertaken. During this early stage, however, we describe the project and tentatively approach its data and potential health benefits while drawing on the affordances of postcritical thinking and an analysis centered on what we call literary connectivity.